1965
DOI: 10.1136/adc.40.213.513
|View full text |Cite
|
Sign up to set email alerts
|

Blood 5-hydroxytryptamine levels in the newborn.

Abstract: During the course of a long-term investigation, still in progress, designed to shed light on the observation of Pare, Sandler, and Stacey (1960) that certain children with mental handicap have high blood 5-hydroxytryptamine (5HT) concentrations, some data on levels in normal newborn infants were obtained which seem to be worthy of record. MethodWhole-blood 5HT levels were measured by the method of Contractor (1964) with the following modifications. (a) Capillary blood obtained from the heel with minimal sque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1966
1966
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The platelet 5-HT ontogeny results are in good agreement with the limited prior reports of levels in newborns and infants, both in terms of the absolute levels observed and the apparent early low levels (32)(33)(34)(35)(36). Although most previous studies have reported 5-HT concentrations in units of ng/mL, the tendency for ng/mL values to positively correlate with platelet count, observed here and elsewhere (37) 420 platelets unit of concentration is preferred and a greater effort should be made to use this form of expression.…”
Section: Discussionsupporting
confidence: 80%
“…The platelet 5-HT ontogeny results are in good agreement with the limited prior reports of levels in newborns and infants, both in terms of the absolute levels observed and the apparent early low levels (32)(33)(34)(35)(36). Although most previous studies have reported 5-HT concentrations in units of ng/mL, the tendency for ng/mL values to positively correlate with platelet count, observed here and elsewhere (37) 420 platelets unit of concentration is preferred and a greater effort should be made to use this form of expression.…”
Section: Discussionsupporting
confidence: 80%
“…The concentration of this amine was very close to that found in the neonatal period by Berman et al (1965) and Hazra et al (1965).…”
Section: Discussionsupporting
confidence: 56%
“…1 and the Table. The value of this ratio is high in early infancy, falling to a lower level at 1 year. The high initial value of the ratio is due to an increased rate of 5HIAA excretion in early infancy and coincides with the rising levels of whole blood 5HT occurring during this period (Hazra, Benson, and Sandler, 1965). The subsequent decrease in ratio is not due to an absolute decrease in 5HIAA excretion, but to a reduced increment rate, accompanied by a constantly increasing creatinine excretion rate.…”
Section: Resultsmentioning
confidence: 72%